Rapid Expansion of Phenylthiocarbamide Non-Tasters among Japanese Macaques - Suzuki-Hashido, Nami (PLoS One, 2015)
Bitter taste receptors (TAS2R proteins) allow mammals to detect and avoid ingestion of toxins in food. Thus, TAS2Rs play an important role in food choice and are subject to complex natural selection pressures. In our previous study, we examined nucleotide variation in TAS2R38, a gene expressing bitter taste receptor for phenylthiocarbamide (PTC), in 333 Japanese macaques (Macaca fuscata) from 9 local populations in Japan. We identified a PTC “non-taster” TAS2R38 allele in Japanese macaques that was caused by a loss of the start codon. This PTC non-taster allele was only found in a limited local population (the Kii area), at a frequency of 29%. In this study, we confirmed that this allele was present in only the Kii population by analyzing an additional 264 individuals from eight new populations. Using cellular and behavioral experiments, we found that this allele lost its receptor function for perceiving PTC. The nucleotide sequences of the allele including flanking regions (of about 10 kb) from 23 chromosomes were identical, suggesting that a non-taster allele arose and expanded in the Kii population during the last 13,000 years. Genetic analyses of non-coding regions in Kii individuals and neighboring populations indicated that the high allele frequency in the Kii population could not be explained by demographic history, suggesting that positive selection resulted in a rapid increase in PTC non-tasters in the Kii population. The loss-of-function that occurred at the TAS2R38 locus presumably provided a fitness advantage to Japanese macaques in the Kii population. Because TAS2R38 ligands are often found in plants, this functional change in fitness is perhaps related to feeding habit specificity. These findings should provide valuable insights for elucidating adaptive evolutionary changes with respect to various environments in wild mammals.